Arti penting dan implementasi hukum perizinan dalam bidang lingkungan hidup di Indonesia - Eny Kusdarini (Jurnal Civics: Media Kajian Kewarganegaraan, 2005)
Licensing represent one of the medium of yuridis vitally administrative in execution of effort activity of development, especially in its bearing with continuation of ability of environment in this Indonesia Circumstance to earn us of the understand remember with gift of permission, governmental can instruct and control its citizen to obviate self-damage of environment in consequence of execution of development of which can result change of environment function. But efficacy of licensing as medium of yuridis administrative in continuation of ability of this environment cannot be discharged from situation of state administration government officer and enforcer government officer punish as executor of effectiveness punish in everyday life. If them apply licensing law better and also apply sanction emphatically to lawbreaker of licensing undoubtedly continuity of ability of Indonesia environment will be able to be looked after from generation to generation